Nitrate poisoning in ruminants - KATSOULOS (Π. Δ. ΚΑΤΣΟΥΛΟΣ) P. D.; PANOUSIS (Ν. ΠΑΝΟΥΣΗΣ) N.; KARATZIAS (Χ. ΚΑΡΑΤΖΙΑΣ) H. (Journal of the Hellenic Veterinary Medical Society, 2017)
This paper describes the nitrate - nitrite poisoning of ruminants. This disease is caused by the ingestion of large amount of nitrate salts, which are reduced in the rumen to nitrite ions. Nitrites, after their absorption, cause the formation of methemoglobin and, in turn, respiratory and circulatory distress. The aim of the treatment is to reduce the percentage of methemoglobin in blood and to stop the continuing production of nitrite ions in the rumen. For the prevention of the disease, avoidance of feedstuff rich in nitrates and improvement of the water quality, are suggested.